EFEKTIVITAS CANGKANG TELUR AYAM NEGERI (Gallus gallus domesticus) SEBAGAI ADSORBEN TERHADAP DAYA JERAP LOGAM BERAT MERKURI (Hg2+) - Fajar Muhammad; Yusriani Sapta dewi (JURNAL TECHLINK, 2020)
Industrial development increases pollution in the environment, while the results of industrial wastedisposal generally produce waste containing heavy metals, one of which is mercury (Hg). Eggshell iswaste originating from households and the food industry which is made from eggs and has the potentialas an adsorbent to absorb mercury ions (Hg2 +). In this study, egg shells were prepared with twotreatments: egg shell adsorbent and with eggshells activated by 30% NaOH after heating in a furnaceat 600 oC for 2 hours then mashed with a particle size of 200 mesh. The adsorbent is then used toabsorb Hg2 + ions from the Hg (NO3) 2 compound. H2O as much as 0.01 ppm with the activatedeggshell and eggshell adsorbent weight of 2 grams each, where the adsorption process is carried outwith 2 contact times, namely 60 minutes and 120 minutes and tested with a Mercury Analyzer. Theadsorption process obtained, the optimum at the contact time of 120 minutes and the eggshell adsorbenttreatment with an average percentage of 93.931%.